Contrast-enhanced ultrasound combined with elastic imaging for predicting the efficacy of concurrent chemoradiotherapy in cervical cancer: a feasibility study - Ma, Yujuan; Zhao, Xuebo; Chen, Xianxia (Frontiers in Oncology, 2024)
Objective Contrast-enhanced ultrasound (CEUS) and elastography are of great value in the diagnosis of cervical cancer (CC). However, there is limited research on the role of contrast-enhanced ultrasound combined with elastography in predicting concurrent chemoradiotherapy and disease progression for cervical cancer. The purpose of this study was to evaluate the feasibility of contrast-enhanced ultrasound combined with elastography and tumor prognosis. Methods MRI was performed on 98 patients with cervical cancer before and after treatment. Before, during, and 1 week after the treatment, contrast-enhanced ultrasound and elastography were conducted, and the alterations of ultrasound-related parameters at each time point of the treatment were compared. The correlation between contrast-enhanced ultrasound combined with elastic imaging and oncological outcome was assessed. Results There was no notable difference in overall clinical data between the complete remission (CR) group and the partial remission (PR) group (P>0.05). Before treatment, there were no statistically significant differences in elasticity score, time to peak (TTP), and peak intensity (PI) between the CR group and the PR group. However, there were no statistical differences in elastic strain ratio (SR) and area under the curve (AUC) before and after treatment between the CR group and the PR group, and there were also no statistical differences in the elastic strain ratio (SR) and area under the curve (AUC) of contrast-enhanced ultrasound parameters between the CR group and the PR group before and during treatment. There was a statistically significant difference after treatment (P<0.05).At present, the follow-up of patients is about 1 year, 7 patients were excluded due to loss to follow-up, and 91 patients were included in the follow-up study. Through the review of the cases and combined with MRI (version RECIST1.1) and serology and other related examinations, if the patient has a new lesion or the lesion is larger than before, the tumor marker Squamous cell carcinoma antigen (SCC-Ag) is significantly increased twice in a row, and the patient is divided into progressive disease (PD). Those who did not see significant changes were divided into stable disease (SD) group. The relationship between clinical characteristics, ultrasound parameters and disease progression in 91 patients was compared. There was no significant difference in age and clinical stage between the two groups (P>0.05), but there was a significant difference in the elevation of tumor marker squamous cell carcinoma antigen (SCC-Ag) between the two groups (P<0.05).With the growth of tumors, TTP decreased, elasticity score and PI increased, and the difference was statistically significant (P<0.05). The AUC of SCC-Ag was 0.655, the sensitivity was 85.3%, and the specificity was 45.6%.The AUC, sensitivity and specificity of ultrasound parameters combined with SCC-Ag predicted disease progression was 0.959, 91.2% and 94.8%. Conclusions Using contrast-enhanced ultrasound and elastography to predict the efficacy and disease progression of concurrent chemoradiotherapy is feasible. In addition, the combination of SCC-Ag with contrast-enhanced ultrasound and elastography can further enhance the efficiency of predicting disease progression.